(untitled) (Ha Noi, 1994)
The proceeding collects papers presented at the workshop on reforestation and afforestation of mangroves in Vietnam held at Can Gio, Ho Chi Minh city. The papers focus on conditions, reasons for and consequences of the reduction of mangroves of Vietnam. The papers also provide the results in restoring and planting the forests technical method and experience, initial results in nursery garden formation, some results in growth, biomass, the fluence of salinity on the growth ability, fruiting cycles and mature propagules of some essential species
Keywords: Mangrove forests,Mangrove restoration,Rừng ngập mặn,Khôi phục rừng ngập mặn; Vietnam,Vietnam,Việt Nam,Việt Nam